2009
DOI: 10.1080/00268970802649591
|View full text |Cite
|
Sign up to set email alerts
|

Group theoretical treatment of Jahn–Teller versus spin-orbit effects on geometries, rovibronic levels and nuclear spin species of bismuth and antimony clusters

Abstract: To cite this article: Krishnan Balasubramanian (2009) Group theoretical treatment of Jahn-Teller versus spin-orbit effects on geometries, rovibronic levels and nuclear spin species of bismuth and antimony clusters, Clusters of very heavy group 15 elements, particularly those of Sb and Bi are intriguing due to the interplay of vibronic and relativistic effects, which quench the Jahn-Teller distortion, and thus resulting in the retention of higher symmetry in the double group. Group theoretical treatment of Bi n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Relativistic effects are known to make significant contributions to the electronic structure spectra and optical properties of molecules containing very heavy atoms [45][46][47][48][49]. Consequently, relativistic effects such as mass-velocity, Darwin and spin-orbit effects are expected to be significant for Bi-containing molecules, as shown in previous studies [46][47][48][49].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Relativistic effects are known to make significant contributions to the electronic structure spectra and optical properties of molecules containing very heavy atoms [45][46][47][48][49]. Consequently, relativistic effects such as mass-velocity, Darwin and spin-orbit effects are expected to be significant for Bi-containing molecules, as shown in previous studies [46][47][48][49].…”
Section: Introductionmentioning
confidence: 66%
“…Relativistic effects are known to make significant contributions to the electronic structure spectra and optical properties of molecules containing very heavy atoms [45][46][47][48][49]. Consequently, relativistic effects such as mass-velocity, Darwin and spin-orbit effects are expected to be significant for Bi-containing molecules, as shown in previous studies [46][47][48][49]. Furthermore, Bi is quite interesting from a relativistic standpoint since its electronic configuration 6s 2 6p 3 suggests that the 6s 2 part of the valence shell is inert due to the relativistic contraction of the 6s orbital.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic clusters in their ground-state geometries can present Jahn–Teller (JT) and pseudo-Jahn–Teller (PJT) effects that break the orbital symmetry. It has been shown that DFT methods can handle the JT and PJT contributions in geometry optimizations, reproducing the breaking of high-symmetry configurations in metallic clusters; , however, spin–orbit effects could compensate for JT contributions, producing high-symmetry structures. , JT distortions are present in both the GS and MECP geometries in Al 6 clusters. As can be seen in Table , SO coupling makes a low-energy contribution in Al 6 [14 cm –1 (i.e., 0.04 kcal/mol) on the g CP–3 geometry].…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] These large spin‐orbit effects manifest themselves in the optical, trion, and excitonic properties and spin valley dynamics of WS 2 , all of which are attributed to the large spin‐orbit splitting of W. Spin‐orbit effects not only influence the geometries of the molecules and materials containing heavy atoms but also completely alter the topological structures of potential energy surfaces. [ 36,37 ] That is, the spin‐orbit coupling is so large that it overtakes Jahn‐Teller distortions, thus modifying the potential energy surfaces of such molecules. [ 37 ] This arises from the fact that the overall symmetry of the molecule or material under consideration is altered when spin‐orbit coupling is included from the usual point group to the double group, [ 9,37 ] thereby allowing for the mixing of two electronic states that would otherwise not mix.…”
Section: Molybdenum and Tungsten Disulfidesmentioning
confidence: 99%
“…[ 36,37 ] That is, the spin‐orbit coupling is so large that it overtakes Jahn‐Teller distortions, thus modifying the potential energy surfaces of such molecules. [ 37 ] This arises from the fact that the overall symmetry of the molecule or material under consideration is altered when spin‐orbit coupling is included from the usual point group to the double group, [ 9,37 ] thereby allowing for the mixing of two electronic states that would otherwise not mix. Such singlet‐triplet mixings of electronic states caused by spin‐orbit coupling result in very interesting topological spintronics in heavy materials such as WS 2 .…”
Section: Molybdenum and Tungsten Disulfidesmentioning
confidence: 99%